Jigsaw in Teaching Reading for Elementary School Students - Handayani, Made Sonia; Widana, I Kadek Wahyu; Febiyanti, Ni Wayan (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
The current study investigated the effect of jigsaw on students’ reading comprehension. In doing the study, the pretest and posttest design was used. The participants of the study were 6th grade students in one public school in Singaraja, Bali. Through descriptive analysis, it was found that the mean score of pre-tests was 66.25, and the posttest was 75.42. The mean difference between pretest and posttest was 9.17. The result of paired sample t test showed a significant value (Sig. 2-tailed=.000). Thus, it can be concluded that jigsaw technique significantly affected students’ reading comprehension. English teachers are encouraged to implement jigsaw technique in classroom.